Exploring Multiple Forms of Intimate Partner Violence in a Gender and Racially/Ethnically Diverse Sample of Transgender Adults. Issue 19 (October 2021) - King, Wesley M.; Restar, Arjee; Operario, Don
Intimate partner violence (IPV) is highly prevalent in transgender (trans) populations in the United States; however, details about its manifestations and correlates have not been well captured. Using data from the 2015 U.S. Transgender Survey, we analyzed weighted data from 23, 999 adult transgender participants to estimate the prevalence and explore correlates of five IPV subtypes: psychological IPV, physical IPV, trans-related IPV, stalking, and forced sex committed by an intimate partner. Regression models examined race/ethnicity, gender identity, past-year incarceration, past-year sex work, and lifetime homelessness, and adjusted for annual household income, highest level of education, age, birthplace, Census region, and relationship status. The sample was racially/ethnically diverse (62.6% White, 0.7% Alaskan Native/American Indian, 4.7% Asian/Native Hawaiian/Pacific Islander, 12.7% Black/African American, 16.5% Latinx/Hispanic, 0.4% Middle Eastern/North African, 2.5% Multiracial/Not Listed), and comprised of 31.2% transgender men, 34.2% transgender women, 27.5% assigned-female-at-birth nonbinary participants, and 7.1% assigned-male-at-birth nonbinary participants. Rates of IPV were high, with variability by IPV subtype: 42.0% endorsed psychological IPV, 39.9% endorsed physical IPV, 30.4% endorsed trans-related IPV, 18.0% endorsed stalking, and 21.5% endorsed forced sex by an intimate partner. We observed disparities in IPV subtypes by race/ethnicity, gender identity, and experiences of social marginalization. Results highlight the need for targeted, trans-inclusive IPV screening practices and interventions. Future studies should examine the syndemic effects of IPV, social marginalization, and health outcomes related to HIV, substance use, and mental health in trans populations.